Co-contraction of ankle muscle activity during quiet standing in individuals with incomplete spinal cord injury is associated with postural instability - Kai Lon Fok (Nature Portfolio, 2021)
Abstract Previous findings indicate that co-contractions of plantarflexors and dorsiflexors during quiet standing increase the ankle mechanical joint stiffness, resulting in increased postural sway. Balance impairments in individuals with incomplete spinal cord injury (iSCI) may be due to co-contractions like in other individuals with reduced balance ability. Here we investigated the effect of co-contraction between plantar- and dorsiflexors on postural balance in individuals with iSCI (iSCI-group) and able-bodied individuals (AB-group). Thirteen able-bodied individuals and 13 individuals with iSCI were asked to perform quiet standing with their eyes open (EO) and eyes closed (EC). Kinetics and electromyograms from the tibialis anterior (TA), soleus and medial gastrocnemius were collected bilaterally. The iSCI-group exhibited more co-contractions than the AB-group (EO: 0.208% vs. 75.163%, p = 0.004; EC: 1.767% vs. 92.373%, p = 0.016). Furthermore, postural sway was larger during co-contractions than during no co-contraction in the iSCI-group (EO: 1.405 cm/s2 vs. 0.867 cm/s2, p = 0.023; EC: 1.831 cm/s2 vs. 1.179 cm/s2, p = 0.030), but no differences were found for the AB-group (EO: 0.393 cm/s2 vs. 0.499 cm/s2, p = 1.00; EC: 0.686 cm/s2 vs. 0.654 cm/s2, p = 1.00). To investigate the mechanism, we performed a computational simulation study using an inverted pendulum model and linear controllers. An increase of mechanical stiffness in the simulated iSCI-group resulted in increased postural sway (EO: 2.520 cm/s2 vs. 1.174 cm/s2, p < 0.001; EC: 4.226 cm/s2 vs. 1.836 cm/s2, p < 0.001), but not for the simulated AB-group (EO: 0.658 cm/s2 vs. 0.658 cm/s2, p = 1.00; EC: 0.943 cm/s2 vs. 0.926 cm/s2, p = 0.190). Thus, we demonstrated that co-contractions may be a compensatory strategy for individuals with iSCI to accommodate for decreased motor function, but co-contractions may result in increased ankle mechanical joint stiffness and consequently postural sway.